Evaluation of Students\' Satisfaction with Virtual Education in the Self-Governing Campus of Babol University of Medical Sciences During the Pandemic of COVID-19 - Naghmeh Ziaie; Romina Hamzehpour; Mehran Baghertabar; Sodabeh Alidadi; Maryam Ghaemi Amiri (Babol University of Medical Sciences, 2021)
Background and Objective: Due to the change in educational methods and virtualization of university classrooms following the COVID-19 epidemic, after the necessary activities in this regard, in order to examine students' feedback on what they experienced during the academic year 1399-1400, in this Study we measured the satisfaction of students of Self-Governing Campus of Babol University of Medical Sciences about virtual education. Methods: In this cross-sectional study, the level of students' satisfaction with virtual education and end-of-semester tests was assessed using a researcher-made questionnaire. The poll was conducted through the Faradid system. Results were reported in frequency and frequency percentage. Findings: A total of 250 students with 66.85% participation in 4 fields of general medicine, general dentistry, bachelor of physiotherapy and bachelor of nursingparticipated in the study. The general satisfaction of students with virtual education, and the possibility of establishing a two-way relationship between professors and students and providing appropriate feedback, all 4 disciplines were moderate satisfaction. Regarding the evaluation method at the end of the semester, 84.5% of students had average and lower level of satisfaction. Regarding the preferred teaching method, the choice of students in all fields was face-to-face teaching method. Conclusion: Given the current situation and accepting the fact that education should move towards virtualization, it seems that more decision should be taken to raise the quality of e-learning so that interactive methods can take their place in the method of education.